Adeno-associated virus mediated artificial circular RNA for triggering cancer immunotherapy to treat prostate cancer - Ye, Chujin; Liu, Zhiye; Xie, Qifan; Tang, Yanlin; Zeng, Jiayi; Feng, Ziwei; Liu, Jiumin; Xie, Haibiao (Frontiers in Oncology, 2025)
IntroductionSpecifically regulating endogenous molecules is a potential molecular therapeutic strategy. Naturally occurring circular RNAs (circRNAs) are structurally stable and have been proved to serve as highly efficient miR-sponges and protein-sponges in cancer cells.MethodsWe chemically synthesized circRNA (ScircRNA) in vitro to achieve therapeutic dysfunction by targeting specific miRNAs. RNase R and fetal bovine serum were used to evaluate the stability of ScircRNAs. In prostate cancer cell lines, the competitive inhibition of the ScircRNA on miR-375 and miR-21 activity was evaluated using luciferase report gene, cell proliferation, and apoptosis assays.ResultsWe found that ScircRNAs were more resistant to nuclease digestion and more effective inhibiting target miRNAs than linear RNA sponges. The ScircRNAs inhibited malignant phenotype of prostate cancer by specifically inhibiting the activity of miR-21 and miR-375. In addition, we used the ScircRNA inhibiting CDK5 expression to trigger T-cell mediated cancer immunotherapy for treating prostate cancer in vivo.DiscussionThe ScircRNAs possessed the advantages of stable structure and simple construction, and can specifically inhibit the function of target miRNAs, which has a potential therapeutic application prospect in prostate cancer.